Inflammatory cytokines in and cognitive function of adolescents with first-episode schizophrenia, bipolar disorder, or major depressive disorder. (19th February 2023) - Chen, Mu-Hong; Hsu, Ju-Wei; Huang, Kai-Lin; Tsai, Shih-Jen; Tu, Pei-Chi; Bai, Ya-Mei
Abstract: Background: Few studies have explored the complex relationship of pro- and anti-inflammatory cytokines with cognitive function in adolescents with first-episode schizophrenia, bipolar disorder, or major depressive disorder. Methods: In total, 26, 35, and 29 adolescents with first-episode schizophrenia, bipolar disorder, and major depressive disorder, respectively, and 22 age- and sex-matched controls were included in the current study. Cytokines, namely interleukin (IL)-2, IL-6, tumor necrosis factor (TNF)-α, and C-reactive protein (CRP), were assessed. The Wisconsin Card Sorting Test (WCST) and the working memory task were administered to assess cognitive function. Results: Using generalized linear models with adjustment for demographic data and clinical symptoms, patients with bipolar disorder were found to exhibit the highest levels of CRP ( P = .023), IL-6 ( P = .022), and TNF-α ( P = .011), and had the lowest IL-2 levels ( P = .034) among the four groups. According to the results of the WCST and working memory task, adolescents with schizophrenia exhibited the lowest performance in cognitive function. In addition, among the assessed cytokines, only CRP levels ( P = .027) were negatively associated with WCST scores. Discussion: Dysregulated pro- and anti-inflammatory cytokines and impaired cognitive functioning were observed in first-episode adolescent-onset schizophrenia, bipolar disorder, and major depressive disorder. The altered cytokine profiles may play important roles in the pathophysiology of schizophrenia, bipolar disorder, and major depressive disorder.